Surface Molecular Functionalization of Unusual Phase Metal Nanomaterials for Highly Efficient Electrochemical Carbon Dioxide Reduction under Industry‐Relevant Current Density. Issue 11 (20th January 2022) - Wang, Juan; Yu, Jinli; Sun, Mingzi; Liao, Lingwen; Zhang, Qinghua; Zhai, Li; Zhou, Xichen; Li, Lujiang; Wang, Gang; Meng, Fanqi; Shen, Dong; Li, Zijian; et al.
Abstract: The electrochemical carbon dioxide reduction reaction (CO2 RR) provides a sustainable strategy to relieve global warming and achieve carbon neutrality. However, the practical application of CO2 RR is still limited by the poor selectivity and low current density. Here, the surface molecular functionalization of unusual phase metal nanomaterials for high‐performance CO2 RR under industry‐relevant current density is reported. It is observed that 5‐mercapto‐1‐methyltetrazole (MMT)‐modified 4H/face‐centered cubic (fcc) gold (Au) nanorods demonstrate greatly enhanced CO2 RR performance than original oleylamine (OAm)‐capped 4H/fcc Au nanorods in both an H‐type cell and flow cell. Significantly, MMT‐modified 4H/fcc Au nanorods deliver an excellent carbon monoxide selectivity of 95.6% under the industry‐relevant current density of 200 mA cm −2 . Density functional theory calculations reveal distinct electronic modulations by surface ligands, in which MMT improves while OAm suppresses the surface electroactivity of 4H/fcc Au nanorods. Furthermore, this method can be extended to various MMT derivatives and conventional fcc Au nanostructures in boosting CO2 RR performance. Abstract : Surface molecular functionalization of unusual phase gold (Au) nanorods with 5‐mercapto‐1‐methyltetrazole (MMT) significantly enhances the electrochemical CO2 reduction reaction (CO2 RR) performance in an H‐type cell and flow cell, especially under industry‐relevant current density of 200 mA cm −2, comparing to original Au nanorods. This facile surface molecular functionalization strategy is applicable to various MMT derivatives and conventional Au nanostructures in boosting CO2 RR performance.